Tuning the caloric response of BaTiO3 by tensile epitaxial strain. (26th September 2016) - Grünebohm, Anna; Marathe, Madhura; Ederer, Claude
Abstract: We investigate the effect of epitaxial strain on the electrocaloric effect (ECE) in BaTiO3 by means of ab-initio –based molecular-dynamics simulations. We show that tensile strain can be used to optimize the operation range for ferroic cooling. Strain in the range of ≤ 1% can be used to shift the operation temperature by several hundreds of kelvin both to higher and lower temperatures, depending on the direction of the external field. In addition, the transformation between multi-domain and mono-domain states, induced by an in-plane electric field, results in an additional peak of the adiabatic temperature change at lower temperatures, and a broad temperature interval where the caloric response scales linearly with the applied field strength, even up to very high fields.